Computational aspects of the finite difference method for the time-dependent heat equation - Sequeira-Chavarría, Filánder (2019)
In this paper we describe in detail an algorithm for the efficient computational implementation of the finite difference method (FDM) in the two-dimensional time-dependent heat equation with non-homogeneous Dirichlet boundary conditions. The MATLAB® software was used to validate the method mentioned here; however, the processes are presented independently from the programming language. Finally, numerical results are presented to validate the proposed algorithm.